Environmental Toxicants and Infant Mortality in the USA - David Kennedy; Stephanie Seneff; Robert M Davidson; John W Oller Jr; Boyd E Haley; Roger D Masters (Open Journal of Biological Sciences - Peertechz Publications, 2016)
Despite enjoying a high standard of living, the United States ranks 46th among nations reporting infant survival rates to the World Health Organization. Among factors that increase infant mortality are  environmental toxicants. Toxic metals such as mercury, aluminum, and lead interact synergistically with fluoride compounds to produce metal fluoride complexes (e.g., AlF3 and AlF4−). Such toxicants act as biophosphate mimetics disrupting biological signaling processes governing development, immune defenses, and ordinary maintenance systems. Sources for the metals include mother's mercury amalgams, mercury and aluminum in injected medicines, and lead contaminated drinking water. All of them are made even more toxic by fluorides as evidenced recently by water contamination in Flint, Michigan. Fluorides interact with other toxins increasing their harmful impact. Among the interactants are glyphosate and phosphate containing fertilizers that end up in the food and water because of their widespread use in agriculture. The negative synergy for neonates in the U.S. is increased by the hepatitis B injection containing both mercury and aluminum, and infant formula contaminated with aluminum and the glyphosate in genetically modified soy milk reconstituted with water containing fluoride, aluminum, lead, and other toxic substances. The harmful interactions of such chemicals are associated with rising infant mortality in the U.S. We propose, therefore, a modest but urgent policy change: under TSCA §5, silicofluoride addition to public water supplies should be suspended.